Modern Medicine and Pharmaceutics - Rehan Haider; Asghar Mehdi; Anjum Zehra; Geetha Kumari Das; Zameer Ahmed; Sambreen Zameer (International Journal of Integrative Sciences, 2024)
Modern Medicine and pharmaceuticals have made tremendous strides in enhancing the healthcare and quality of life of people worldwide. This summary explores the key traits and trends in these fields. In recent decades, current medications have witnessed a paradigm shift toward personalized healthcare. Improvements in genomics, proteomics, and record analytics have paved the way for precision medication and tailoring treatments for an individual's genetic makeup. This technique enhances treatment efficacy while minimizing aspect consequences, marking a significant departure from the one-size-fits-all approach. Pharmaceutical research has experienced a revolution with the advent of biotechnology. Biopharmaceuticals, along with monoclonal antibodies and gene treatment plans, have emerged as powerful tools for the fight against formerly untreatable illnesses. Their ability to target specific molecules or genes has opened new frontiers in cancer treatment, uncommon illnesses, and autoimmune diseases. Furthermore, pharmaceutical enterprises have embraced virtual technologies. AI-pushed drug discovery, in silico medical trials, and telemedicine reshape the drug development pipeline and improve the care of affected persons. In particular, telemedicine has gained prominence, presenting available healthcare offerings and far-flung tracking. However, these advancements have moral and regulatory demands. Privateness issues, information protection, and equitable access to present-day remedies remain essential issues. The need for strong moral frameworks and regulatory oversight is paramount